IMPLEMENTASI HAWALAH PADA PEMBIAYAAN BERMASALAH STUDI KASUS KOPERASI JASA KEUANGAN SYARIAH USAHA GABUNGAN TERPADU BMT SIDOGIRI KCP OMBEN TAHUN BUKU 2018 - Abdul Majid Toyyibi (JURNAL PROFIT, 2019)
Financing is the most important part of the milestone of an Islamic financial institution, its existence must be able to avoid the problematic financing that can hamper the value of its income. So that the existence of hawalah contract becomes a new solution in minimizing problem financing. So that in this study there are two formulations of the problem namely the practice of hawalah by reviewing the MUI fatwa and the type used by BMT Sidogiri. The research method used is descriptive qualitative in which the researcher descends directly to the study site by conducting interviews and collecting primary and secondary data sources as a complement and then from there an analysis of the data is conductedAs for the results of his research that the pillars and legal requirements of the law in KJKS UGT BMT Sidogiri KCP Omben are in accordance with the pillars and conditions according to Islamic economics and the MUI DSN fatwa regarding hawalah DSN MUI fatwa which has been decided related to hawalah. The implementation of hawalah, which is between muhil and muhal alayh, comes to KJKS UGT BMT Sidogiri KCP Omben to provide information that installments that are borne by the muhil parties will be continued with the financing installments by the muhal alayhi when legally obliged to fulfill the conditions and regulations.